Supermartensitic stainless steel deposits: shielding gas and post-weld heat treatment: detailed are the results as CO2 content in the shielding gas increased, plus the postweld heat treatment utilized in this work - Zappa Maidana, Norberto Sebastián (2013)
Welding supermartensitic stainless steel plays a crucial role in structural components, influencing their toughness and resistance to sulfide stress cracking. Postweld heat treatment (PWHT) adjusts the final properties of the weldments, bearing on microstructural evolution. The objective of this work was to study the effects of different shielding gas mixtures and PWHT on supermartensitic stainless steel allweld-metal properties. Three all-weld-metal test coupons were prepared according to standard ANSI/AWS A5.22:95, Specification for Stainless Steel Electrodes for Flux Cored Arc Welding and Stainless Steel Flux Cored Rods for Gas Tungsten Arc Welding, using a 1.2-mm-diameter tubular, metal-cored wire under Ar-5% He, Ar-2% CO2, and Ar-18% CO2 gas shielding mixtures in the flat position with a nominal heat input of 1 kJ mm–1. The PWHT used was 650°C for 15 min. All-weld metal chemical composition analysis, metallurgical characterization, hardness and tensile property measurements, and Charpy V-notch tests were carried out. It was found that as CO2 increased in the shielding gas C, O, and N contents increased as well as mechanical properties varied; hardness and ultimate tensile strength increased, and toughness decreased. The PWHT improved toughness. Technological property of the consumable was also studied.